The Ethical and Economic Impact of Defaults - Siegel, Mark D.; Stapleton, Renee; Wunsch, Hannah (Seminars in Respiratory and Critical Care Medicine, 2012)
Medical care offered to the critically ill often occurs by default, unfolding automatically unless concerted effort is made to do otherwise. In their scope, defaults include traditional approaches to treatment and decision making, as well as policies deliberately set to promote specific health outcomes. Defaults are ethically sound to the extent that they foster patient well-being and autonomy. Unfortunately in practice, some defaults lead to ineffective, unwanted, and expensive care. This article reviews the ethical and economic impact of defaults, paying special attention to their influence on the practice of cardiopulmonary resuscitation and admission to the intensive care unit.
Keywords: default; cardiopulmonary resuscitation (CPR); intensive care unit (ICU) admission; behavioral economics; decision making